On epidote fission track dating - Curvo, EAC; Hadler, J. C.; Iunes, P. J.; Guedes, S.; Tello, CAS; Paulo, SR; Hackspacher, P. C.; Palissari, R.; Moreira, PAFP (Elsevier B.V., 2005)
The use of epidote in fission track dating was abandoned since the beginning of the 1980s due to difficulties like absence of a standard etching procedure, obtainment of different closure temperatures and the percentage of the datable samples. The results become much more reproducible when restricting fission track analysis to a peculiar kind of track. We are also studying confined track length, what makes possible to obtain information about fossil track annealing. Fission tracks in epidote were successfully etched with 48% HF at 35 degrees C for 12.5 min. Dating samples by the external detector method was not possible due to problems in measuring the efficiency factor held between the number of fossil fission tracks and tracks induced in mica. Dating a sample from Brejui, RN, Brazil with the population method gave a corrected age of 510 +/- 69Ma, in agreement with published U/Th-Pb ages. From the fact that the fossil track length histogram was bimodal, we were able to infer that this sample registered a thermal episode during its history.These preliminary results indicate that epidote deserves further studies to establish whether it can be employed as a thermochronological tool. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: epidote; fission track dating; brejui epidote; Borborema province-Brazil